Stratification of Returns to Higher Education in Peru: The Role of Education Quality and Major Choices - Alan Sanchez; Marta Favara; Catherine Porter (Institute of Labor Economics (IZA), 2021)
In the last two decades, access to higher education has increased substantially in Latin America. The quantity of new programs available has created concerns about education quality, which has implications for the labor market. We use rich longitudinal data from a Peruvian cohort tracked from ages 8 to 26 (the Young Lives study) to analyze the profile of students enrolled in different 'types' of higher education, and to explore the returns to higher education before and during the COVID-19 crisis. We find evidence of stratification at higher education level: (a) students from the wealthiest households tend to enroll in universities (as opposed to technical institutes), and choose majors and institutions with the highest income rewards; (b) students with higher levels of cognitive skills and socio-emotional competencies tend to attend better quality universities; (c) there are hidden gender gaps: females are more likely to enroll in majors that are the least rewarded in the labor market. In the 2020 labor market, by age 26 we find that: (d) pre-COVID, positive returns to higher education are only observable for those that attended better quality universities; (e) during the pandemic, higher education became a protective factor, with the income premium being higher for everyone that attended this education level; (f) the male income premium doubled during the pandemic.
Keywords: I2; I23; I26; 330; higher education; returns to higher education; COVID-19; Young Lives; Peru